The limits of pious families: Religion, family and the state in the women's pages of Utusan Malaysia (1987–98). (1st June 2019) - Randhawa, Sonia
Between 1987 and 1998, the Malay-language press experienced what appears to be a golden age for media freedom in Malaysia, despite authoritarian legislation. Secure in its support, bolstered by unprecedented economic growth, the government allowed limited criticism and debate. The Malay-Muslim family, however, was seen as increasingly under threat from rapid modernization and the (perceived) influx of women into the workforce. In this milieu, women were expected to shoulder multiple burdens in the home and the workforce. In this context, the women's pages of the Malay-language daily newspaper Utusan Malaysia policed the makeup of the family, helping women, in particular, make sense of their role as pious wives and mothers and as businesswomen and entrepreneurs. Employing critical discourse analysis of articles published during this period, this article illuminates the workings of power, paying attention to the language used in the articles and the context within which they were written. This article summarizes how the Malay-Muslim family evolved, the shifting role of religion as a marker of the Malay-Muslim family and the strains that domestic policies placed on the Malay-Muslim family. I argue that increasing bureaucratization of Islam increased the burden of responsibilities borne by women, while providing limited redress.